Carbon Nano Fibre Reinforcements In Concrete (Indonesian Journal of Science and Technology, 2024)
Graphite nanomaterials offer distinct advantages over micro scale reinforcing fibers in terms of engineering properties and geometric attributes. Through dispersion and effective interfacial interactions of proper functionalization of carbon nanofibers are the prerequisites for their effective use in high-performance cementitious matrices. Furthermore, the use of nano- and micro-scale reinforcements together provides reinforcing effects at different scales, thus rendering balanced gains in engineering properties of the matrix. However, their uses in coarser high-performance matrices have not been evaluated thoroughly. The results show improvements in all flexural attributes, impact and abrasion resistance of concrete with addition of 0.16% of oxidized and polyacrylic acid physisorbed carbon nanofibers, over the corresponding properties of plain matrix. The results also pointed to synergetic effects of hybrid reinforcements on improving the various engineering properties of DSP concrete matrix, especially with low modulus polypropylene microfibers.